Między prawdą a zmyśleniem, czyli wokół feature i reportaży radiowych - Kowalska, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
In this essay, I describe the history of radio reportage. For me, its most interesting aspect is the fact that this genre has been changing over the years from reports based on authentic stories to features with fiction added. The latest form includes as much artistic means of expression and fiction as pure information. This leads to the question: Is a feature – radio documentary with fiction added – the opposite to the classic Polish understanding of reportage as an information genre? Some Polish radio documentaries and most of those in the West are features, so they are partly fictional. It is not clear what should we call “fiction”. For now this is only a proposal, but it provides a first step.